The Relative Frequency of Iron Deficiency Anemia and its Correlation with Pulmonary Function in Children with Cystic Fibrosis - Goudarzipour, Kourosh; Mirzadeh, Hanieh Sadat; Sadr, Saeed; Abdollah Gorji, Fatemeh; Shahrbaf, MohamadAmin (Student Research in Translational Medicine, 2020)
Background and Aims: The prevalence of iron deficiency is increasing in the population of cystic fibrosis patient (CF). The aim of this study was to determine the prevalence of iron deficiency anemia and its correlation with pulmonary function in cystic fibrosis patients. Materials and Methods: This descriptive-analytic study was done on the patients with cystic fibrosis who were referred to the Mofid Children Hospital, Tehran, Iran during 2015-2016. Complete blood counting and iron indices were evaluated; furthermore, Pulmonary function test was performed in ≥5 years old patients to determine the forced expiratory volume in first second (FEV1), forced vital capacity (FVC), FEV1/FVC and forced expiratory flow (FEF25-75). The data were analyzed by SPSS software. Pearson correlation coefficient, t-test, Fisher's exact test and χ2 were used for analyzing data. Results: Among 30 patients who were able to perform spirometry, Spirometric findings were normal in 12 patients (40%) which 72% of them were female. There was a statistically significant correlation between the spirometric findings and the gender of the patients (P<0.05), but the correlation between the gender and iron indices was not significant (P>0.05). Moreover, there was no statistically significant correlation between spirometric findings and iron indices (P> 0.05). Conclusion: There was no significant correlation between iron deficiency and pulmonary function in cystic fibrosis patients.